Lung Abscess - C. Koegelenberg (South African Family Practice)
Lung abscesses are most frequently caused by mouth anaerobes and may arise as a complication of aspiration pneumonia. Patients may present with a productive cough of foul smelling sputum with or without associated digital clubbing.